Repurposing of Rutan showed effective treatment for COVID-19 disease - Shavkat I. Salikhov; Ibrokhim Y. Abdurakhmonov; Yuliya I. Oshchepkova; Jamolitdin F. Ziyavitdinov; Nodir Sh. Berdiev; Haji Akber Aisa; Jingshan Shen; Yechun Xu; H. Eric Xu; Xiangrui Jiang; Leike Zhang; Natalia L. Vypova; et al. (Frontiers in Medicine, 2023)
Previously, from the tannic sumac plant (Rhus coriaria), we developed the Rutan 25 mg oral drug tablets with antiviral activity against influenza A and B viruses, adenoviruses, paramyxoviruses, herpes virus, and cytomegalovirus. Here, our re-purposing study demonstrated that Rutan at 25, 50, and 100 mg/kg provided a very effective and safe treatment for COVID-19 infection, simultaneously inhibiting two vital enzyme systems of the SARS-CoV-2 virus: 3C-like proteinase (3CLpro) and RNA-dependent RNA polymerase (RdRp). There was no drug accumulation in experimental animals’ organs and tissues. A clinical study demonstrated a statistically significant decrease in the C-reactive protein and a reduction of the viremia period. In patients receiving Rutan 25 mg (children) and 100 mg (adults), the frequency of post-COVID-19 manifestations was significantly less than in the control groups not treated with Rutan tablets. Rutan, having antiviral activity, can provide safe treatment and prevention of COVID-19 in adults and children.Clinical Trial RegistrationClinicalTrials.gov, ID NCT05862883.